2007
DOI: 10.1128/aem.00531-07
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium tumefaciens fur Has Important Physiological Roles in Iron and Manganese Homeostasis, the Oxidative Stress Response, and Full Virulence

Abstract: In Agrobacterium tumefaciens, the balance between acquiring enough iron and avoiding iron-induced toxicity is regulated in part by Fur (ferric uptake regulator). A fur mutant was constructed to address the physiological role of the regulator. Atypically, the mutant did not show alterations in the levels of siderophore biosynthesis and the expression of iron transport genes. However, the fur mutant was more sensitive than the wild type to an iron chelator, 2,2-dipyridyl, and was also more resistant to an iron-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 68 publications
1
53
4
Order By: Relevance
“…In particular, increased sensitivity to H 2 O 2 correlates with increased available cellular iron (66). The iron-activated antimicrobial streptonigrin has also been used to approximate the iron state of several bacterial species, with an increased SNG sensitivity implying an increased available cellular iron (33,43,70). In A. tumefaciens, it has previously been shown that a disruption of rirA results in an increased sensitivity to both H 2 O 2 and SNG, and it has been suggested that increased sensitivity is due to increased iron concentrations in the cell (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, increased sensitivity to H 2 O 2 correlates with increased available cellular iron (66). The iron-activated antimicrobial streptonigrin has also been used to approximate the iron state of several bacterial species, with an increased SNG sensitivity implying an increased available cellular iron (33,43,70). In A. tumefaciens, it has previously been shown that a disruption of rirA results in an increased sensitivity to both H 2 O 2 and SNG, and it has been suggested that increased sensitivity is due to increased iron concentrations in the cell (43).…”
Section: Discussionmentioning
confidence: 99%
“…tumefaciens encodes homologues of fur, rirA, and irr, as well as a large cluster of genes that directs the synthesis of a siderophore (20,54,72). The A. tumefaciens fur homologue is reported to primarily regulate manganese uptake and plays only a minor role in response to iron levels (33,53). The RirA and Irr proteins are in fact the probable iron-responsive regulatory candidates.…”
mentioning
confidence: 99%
“…The disruption of the rirA gene (Atu0201) (34) was performed by the method described previously (14). The internal DNA fragment of the rirA coding region was amplified by PCR with primers BT1201 and BT1202, using Pfu DNA polymerase and genomic DNA isolated from wild-type NTL4 as the template.…”
Section: Molecular Techniquesmentioning
confidence: 99%
“…In some experiments, cells were grown in media with 50 M AS in the presence of either 50 M FeCl 3 or an iron chelator, 50 M Dy. Cells were further incubated at 28°C with shaking for 24 h. Cells were harvested, and ␤-galactosidase activity was measured as previously described (14). ␤-Galactosidase activity is presented in units per milligram of protein.…”
Section: Rna Extraction and Reverse Transcriptase Pcr (Rt-pcr) Analysismentioning
confidence: 99%
See 1 more Smart Citation